Uneven development of the lead industry leads to regional differences in blood lead levels of children. (15th January 2022) - Liu, Yang; Xu, Chengdong; Liu, Feiyan; Xiao, Gexin; Zhou, Shaoqi; Huang, Liming; Lin, Ni; Li, Jianyi; Chen, Dong; Fu, Qi; Wang, Huijun; Du, Qingfeng
Abstract: Children's exposure to lead is a global health problem, especially in low- and middle-income countries. However, research on the relationship between children's blood lead levels (BLLs) and the development of the lead industry is still limited. This study examined whether children's BLLs were associated with the development of lead industry in different regions. Using survey data on the BLLs of children living in 250 prefectures in China with corresponding data on their economic factors and lead industries, we explored the regional variation of children's BLLs using statistical methods. The results show that the level of economic development in leaded areas was associated with inequity in children's BLLs and met the environmental Kuznets hypothesis. In areas without lead industries, there was little correlation between the level of economic development and the BLLs of children and thus the environmental Kuznets hypothesis was not supported. Lead mines, lead smelting and chemical companies are major sources of blood lead in children living in leaded areas. This study demonstrated the success of control policies for lead-acid battery manufacturers in promoting the prevention and control of childhood lead poisoning in China. China should consciously support the improvement of children's BLLs in undeveloped areas with lead industries through national financing and policies to avoid the continuous effects of the regional inequality problem of high children's BLLs. Graphical abstract: Image 1 Highlights: Children's BLLs associated with development of regional lead industry in China. The leaded areas met the environmental Kuznets hypothesis. The areas without lead did not meet the environmental Kuznets hypothesis.